1994
DOI: 10.2466/pr0.1994.74.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evidence That Mercury from Silver Dental Fillings May Be an Etiological Factor in Depression, Excessive Anger, and Anxiety

Abstract: Scores on the Beck Depression Inventory were compared for 25 women who had silver dental fillings (amalgams) and for 23 women without amalgams. Women with amalgams had significantly higher scores and reported more symptoms of fatigue and insomnia. Anger scores from the State-Trait Anger Expression Inventory showed that the women with amalgams had statistically significantly higher mean scores on expressing anger without provocation and experiencing more intense angry feelings. The women without amalgams scored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 26 publications
0
18
1
3
Order By: Relevance
“…Mercury intoxication has been reported to provoke changes in personality traits as a symptom of erethism (3,13). Alterations have been reported even at very low exposure concentrations, such as higher trait anxiety scores in women exposed to elemental mercury from dental amalgams compared to women with no dental fillings, attributed to a possible dysfunctional norepinephrine metabolism (40).…”
Section: Discussionmentioning
confidence: 99%
“…Mercury intoxication has been reported to provoke changes in personality traits as a symptom of erethism (3,13). Alterations have been reported even at very low exposure concentrations, such as higher trait anxiety scores in women exposed to elemental mercury from dental amalgams compared to women with no dental fillings, attributed to a possible dysfunctional norepinephrine metabolism (40).…”
Section: Discussionmentioning
confidence: 99%
“…Research on manic patients, on the other hand, has revealed elevated vanadium in the hair, significantly higher levels than those measured in both a control group and a group of recovered manic patients (Naylor et al 1984). Numerous studies have found long-term chronic low doses of mercury cause neurological, memory, behaviour, sleep, and mood problems (Smith 1978;Kishi et al 1994;Siblerud et al 1994;Bittner et al 1998;Echeverria et al 1998). Mercury has been found to strongly inhibit the activity of dipeptyl peptidase (DPP IV), which is required in the digestion of the milk protein casein.…”
Section: Electrolytes and Trace Metalsmentioning
confidence: 99%
“…Chronic exposure to mercury released from silver dental fillings may also produce depression, anxiety and excessive anger as mentioned by Siblerud et al (1994). In another clinical trial, 14 days exposure to dimercaptosuccinic acid (DMSA) produced an initial increase in urinary mercury excretion by 65 percent and one statistical significant effect was a decrease in fatigue-inertia in the DMSA group versus the 36 JOURNAL OF NEUROTHERAPY placebo group (Englund et al, 1994).…”
Section: Discussionmentioning
confidence: 99%